FOODSERVICE WAGING WAR AGAINST COVID-19 CRISIS AND THE OPPORTUNITY - Lim Soon Chow (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
COVID-19 outbreak is threatening the foodservice industry that caused the foodservice operators to shoulder the double burden of fixed cost and zero footfall during the pandemics episode. This best practice review is a simple and effective shortcut for food operators and worth adopting; meanwhile, all these practices provide food for thought by demonstrating what can be done and how to avoid any harm coming to individuals. This bird’s eye view cultivates tactical ideas to policymaker and researcher in dealing with the epidemic episode.